Puss in boots and other stories - Moo-Young, Ian; Perrault, Charles; Grimm, Brothers; Andersen, Hans Christian ([S.l.] : Moo Movies [production company] ; [S.l.] : Longman ELT Video [distributor], 1982)
This fairy tales contains three stories for young learners of English
This videocassette features the three titles: Puss in boots, The four Musicians, The princess and the pea
Editor, Tony Fish, Peter Hearn
Storytellers: John Newton, Anne Rosenfeld
Keywords: Fairy tales; Children's stories, English; Fairy tales -- Film and video adaptations